Studying the Attribution of LiF in OLED by the 𝐶-𝑉 Characteristics - Chun-lin Zhang; Fang-cong Wang; Yong Zhang; Hai-xia Li; Su Liu (International Journal of Photoenergy)
The organic light-emitting device (OLED) with simple structures of indium tin oxide (ITO)/tris(8-quinolinolato) aluminum (Alq3)/LiF/Al and ITO/Alq3/Al was fabricated to analyze the contribution of LiF in OLED. We used the 𝐶-𝑉 characteristics to investigate the contribution of LiF in OLED and found that the capacitance of the above-mentioned structures was 12.5 nF and 77.5 nF, respectively. It is shown that the LiF layer affects the property of OLED resulting in the change of the capacitance of the device.